The hunt for Red October [videorecording (DVD)] - Connery, Sean; Baldwin, Alec, 1958-; Glenn, Scott, 1942-; Jones, James Earl; Neill, Sam; Clancy, Tom, 1947-2013 (Paramount Pictures, 2010)
A new technologically superior Soviet nuclear sub, the Red October, is heading the United States coast under the command of Captain Ramius. The American government thinks Ramius is planning to attack. A lone CIA analyst has a different idea: he thinks Ramius is planning to defect, but he has only a few hours to find him and prove it. At the same time, the entire Russian naval and air commands are trying to find Ramius too.